On the Tribological Performance of Vegetal Lubricants: Experimental Investigation on Jatropha Curcas L. oil. (2016) - Ruggiero, A.; D'Amato, R.; Merola, M.; Valášek, P.; Müller, M.
Abstract: The limited resources of petroleum-based lubricants and increased environmental contamination, that they produce, lead to increased demand for bio-lubricants. Due to several factors such as biodegradability, good lubricating properties and low production costs, the plant oils represent a good alternative as reference to replace the petroleum-based oils. Obviously, the need to ensure the use of vegetable oils as a source of food makes non-edible vegetable oils a formidable source for plant oil lubricants. Thus, the toxicity of Jatropha Curcas L. oil makes it a very attractive and alternative lubricant source. Therefore, the aim of this work is to investigate on tribological performance of Jatropha Curcas L. oil in the lubricating contact pair AISI 52100 steel sliding against X210Cr12 steel. The experimental tests were carried out using ball-on-flat reciprocatory tribometer for several frequencies and with normal load of 12N. The Jatropha Curcas L. oil was analyzed for its chemical and physical properties such as viscosity, density and flash point. The results were interpreted on the basis of the evolution of the friction coefficient. The evolution of the friction coefficient was monitored for 40 min in all tests. The results show that the friction coefficient decreases with the increase of the frequency, and the final value stays in the range of 0.04-0.122.